Knowledge, Attitude, compliance and barriers of immunization among Parents' of under-five children - Prasuna Jelly; Neha Jeenwal; Neha Wadhwa; Nitika Kumari; Pooja Kumari; Pooja Mathur; Pooja Yadav; Pragya Nautiyal; Priyanka Maurya; Priyanka Sarwan; Rakesh Sharma (Elsevier, 2023)
Introduction: Immunization is one of the most substantial contributions from the medical field to human beings as a low-cost intervention to prevent major illnesses that contribute to the mortality of children in developing countries like India. Parent's knowledge plays a vital role in determining the health status of children. Purpose of the study: To assess knowledge, attitude, and compliance of immunization, and explore barriers of immunization among parents of under-five children. Methodology: A cross-sectional study was conducted among 200 parents of under-five children at selected government hospitals in Dehradun district. Study participants were selected by consecutive sampling technique, and data were collected using pre-tested, structured questionnaires. The data was analyzed using descriptive and inferential statistics. Results: Of 200, 39 (19.5%) parents reported that their child was not vaccinated as per schedule. A vast proportion (84.5%) of parents had an average to good level of knowledge regarding under-five immunization. Out of ten components of attitude, most of the parents had agreed in favor of vaccination. The most common barriers of compliance reported by parents were: unaware of the next scheduled doses, illness in family, and absence of vaccine at health centre. Conclusion: Most of the parents of the under-five child had basic knowledge and positive attitude regarding immunization, but the compliance rate for immunization was not 100%. We recommend that health agencies must develop multiple education interventions regarding immunization and periodic reminders for scheduled vaccination for their child. Also, concerned authorities should consider feedback and resolve the issues of parents appropriately.